1999
DOI: 10.1038/sj.gt.3300874
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocyte response against non-immunoselected tumor antigens predicts the outcome of gene therapy with IL-12-transduced tumor cell vaccine

Abstract: The colon adenocarcinoma C26, carrying two endogenous related tumor antigens, whereas nonresponders had CTL tumor-associated antigens (TAA) recognized by CTL, has that recognized preferentially the FR␣ antigen. CD8 from been transduced with the gene coding for the human folate responder mice were characterized to release high levels receptor ␣ (FR␣) as an additional antigen in order to study of granulocyte-macrophage (GM)-CSF upon antigen the efficacy of vaccination against a tumor expressing mulstimulation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“… 141 In this model, administration of a liver pathogen was required to initiate T‐cell‐mediated autoimmune liver destruction 141 . Similarly, multiple strategies have been demonstrated to generate measurable cytotoxic T‐lymphocyte (CTL) responses in patients, without significant correlation to clinical responses 142–144 . The presence of large numbers of transgenic or in vitro ‐expanded tumour antigen‐specific T cells does not consistently cause regression of tumours in animals or patients 145–147 …”
Section: Attraction Of Primed Effector Cells To the Tumour Sitementioning
confidence: 99%
“… 141 In this model, administration of a liver pathogen was required to initiate T‐cell‐mediated autoimmune liver destruction 141 . Similarly, multiple strategies have been demonstrated to generate measurable cytotoxic T‐lymphocyte (CTL) responses in patients, without significant correlation to clinical responses 142–144 . The presence of large numbers of transgenic or in vitro ‐expanded tumour antigen‐specific T cells does not consistently cause regression of tumours in animals or patients 145–147 …”
Section: Attraction Of Primed Effector Cells To the Tumour Sitementioning
confidence: 99%
“…To improve cytolytic activity and IFN-␥ production of tumorprimed CTL, one could envision inclusion of immunostimulatory cytokines in the priming phase (42,43). However, in preliminary experiments, addition of exogenous IL-12 to allogeneic cells resulted in a dramatic inhibition of the expansion of melan-A tetramer ϩ CTL (M. Salio, unpublished results).…”
Section: Figure 7 Cytolytic Activity Of Melan-amentioning
confidence: 99%
“…GM-CSF is vital for antigen presentation (31,32) and has successfully been used as an adjuvant in colorectal cancer vaccine trials (20,21). Vaccination of mice with a tumor cell vaccine indicated that GM-CSF production is a determining factor for treatment efficacy (26).…”
Section: Discussionmentioning
confidence: 99%
“…The concordance for GM-CSF and TNF-a anti-CD55 responses was 9 of 13 (71%). TNF-a and GM-CSF are known to have potent antitumoral effects (25,26). TNF-a induces apoptosis in cancer cells (25).…”
Section: Discussionmentioning
confidence: 99%